Long-run shifts of the Beveridge curve in Peninsular Malaysia, Sabah, and Sarawak - Marcilla Elmy Girl Malasius; James Alin; Mori Kogid (Faculty of Business, Economics and Accountancy, 2021)
Unemployment is one of macroeconomic issue faces by many countries that showing the inefficient use of the capital resources in the market This paper evaluated the Beveridge curve for Peninsular Malaysia, Sabah, and Sarawak. The objectives were to find out the relationship between the unemployment rate and job vacancy rate. A series of job vacancies and unemployment was constructed from year 1982 until 2017. Secondary data (N=35) was analysed using the Simple Linear Regression to find out the causality and correlations between variables. The results shows that both Peninsular and Sarawak has a negative significant relationship between the variables which implies that the shifting of unemployment rate over the year was affected by the job creation. The Beveridge curve was constructed to shows graphical relationship between the job vacancies rate and unemployment rate. This study suggests that economic growth playing an important role through the job creation in way to eradicate the problem of unemployment. In addition, aside from the quantity of job creation, the quality and the location of the job vacancy also took an important role in affecting the number of jobless persons in the labour market.